Sosialisasi Peralatan Kelistrikan dan Pengambilan Keterangan untuk Mengungkapkan Sebuah Kasus di Kepolisian Resort Pidie Sebagai Ahli Elektro - Ramdhan Halid Siregar; Suriadi; Mahdi Syukri; Syahrizal; Syukriyadin; Yuwaldi Away; Alfisyahrin (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
Electricity is very useful for human life. However, if an error in use results in a danger to the safety of humans, livestock and property. Sometimes electricity is also used for special purposes for which there are no guidelines, this will be very risky to safety. As in the case that occurred recently in the Pidie Resort Police area, the Head of the Pidie Resort Police assigned his members for the benefit of the police service in the context of the task of carrying out an examination of electrical experts to obtain information regarding the discovery of a body in the mountain river of Gampong Lhok Broh, Meureudu District, District Pidie Jaya. The expected objectives of this activity are; So that participants can understand the benefits of electrical energy and the basic principles, operation, and maintenance of electrical equipment, Provide participants with knowledge (in general) about how to work and maintain electrical equipment that may be designed and used in a community environment, Demonstrate directly the dangers of some related electrical equipment cases currently being handled by the police. This activity was carried out from October 1 to November 30 2019 and consisted of 3 stages namely; Preparation, Execution, and Compilation of Reports. Based on inspections and field trials in two places, the following conclusions can be drawn; Electric current is dangerous for the human body depending on the amount of current and duration. The effect of electric current on humans starts with tingling/numbness to effect the heart which can cause death. Water is a conductor that can carry electric current properly. The safe voltage limit for humans is 50 Volt AC assuming the human body is 1000 Ohm resistant, the safe current limit for humans is 30 mA. The dedicated team also as electrical experts discusses scientific about matters related to electrical hazards and their effects on the human body.